Guiding principles for teaching Indigenous Australian school students. - McCluskey, Kerryn; Felton, Kathleen (Office for Learning and Teaching, 2015)
Quality teachers are the means for increasing Indigenous students' access and participation in higher and further education. However, teaching in schools with high Indigenous student populations has been reported as a less than desirable option for beginning teachers freshly graduated from university. A current initiative in preservice teacher education is connecting Indigenous students in secondary schools with preservice teachers as in-school tutors who simultaneously develop their teaching skills whilst working at the cultural interface. Yet, not all preservice teachers have opportunity to gain this valuable knowledge and experience. This is a teaching guide developed during a project that collated voices from the field (Indigenous school students, preservice teachers, Indigenous Community Elders who participated in the initiative) describing strategies, approaches and personal stories.